FACTORS THE INFLUENCING STOREY EDUCATION SOCIETY IN KANAGARIAN BONJOL DISTRICT KOTO BESAR REGENCY DHARMASRAYA - Elvira, Elvira; Suarto, Edi; Zahara, Leni (STKIP PGRI Sumbar, 2013)
This research aim to to analyse and know what is there influence between society culture, economics society to storey education society in Kanagarian Bonjol District Koto besar regency Dharmasraya. This Research pertained at type research of korelasional deskiptif. Population in this research is family head residing in Kanagarian Bonjol District Koto besar regency Dharmasraya amounting to 814 family head. Research Sampel in taking by two the way of, regional sampel in taking with technique of purposive sampling, that is election of jorong owning family head which many, while responder sampel in taking with technique of proposional sampling rondum with proportion 15 %, so that the amount of research sampel is 85 family head. Pursuant to analysis of regresi double and correlation hence earning the following disumpulkan: (1) there are influence which is signifikan and is positive cultural society to storey education society in Kanagarian Bonjol District Koto besar regency Dharmasraya because t calculate > t table, strength of low relation (r = 0,308) and given contribution equal to 9,5%, (2) there are influence which is signifikan and is positive economics society to storey education society in Kanagarian Bonjol District Koto besar regency Dharmasraya because t calculate > t table, strength of relation of including lowering ( r = 0,377) and given contribution equal to 14,2%, (3) there are influence which is signifikan and is positive cultural society, economics society to storey education society in Kanagarian Bonjol District Koto besar regency Dharmasraya because t calculate > t table, strength of relation between two the variable to variable of Y the including is (r = 0,411) and given contribution equal to 16,9%.